Gender, Regulation Efficiency and Informal Employment in Sub-Saharan Africa - Akande, Rashidat Sumbola; Kareem, Hauwa K. K. Abdul; Sulaimon, Taofeekat T (Pakistan Journal of Humanities and Social Sciences, 2021)
Regulation efficiency is essential in addressing the growing informal sector in developing countries because informality thrives with an inefficient legal and regulatory framework of an economy. This paper, therefore, seeks to explore the effect of regulations on informal employment across a panel of 36 sub-Saharan Africa from 2005 to 2018. The study includes both the business and labour aspects of regulation to analyse the effect. The fixed effect and GMM method of panel regression analysis was adopted to achieve the objective of the study. The result suggests that an increase in labour regulation efficiency is associated with a reduction in informal employment while there exists no significant relationship between efficient business regulation and informal employment. The study further investigates how the outcomes affect both genders and the output. The study suggests that efficient labour regulation is gender-specific, as the result is only consistent for the male. It is therefore imperative to incorporate more female gender-specific incentives in the social and labour regulations to compensate for the imbalance of social roles of women that may affect their choice to work in the formal or informal sector.